(untitled) (Research, Society and Development, 2021)
Objective: This work aims to analyze scientific articles already made so that we can have greater compliance with the information obtained, in order to develop an study on the effectiveness of low-intensity laser in maxillofacial surgery. Methodology: This narrative literature review uses a qualitative methodology to develop the following research question: Is low-intensity laser effective in maxillofacial surgery? Therefore, the electronic database U.S. National Library of Medicine (PubMed (NLM)) was used, with selection of the following MeSHterms: “Laser therapy”; “Oral surgery”. Inclusion criteria were as follows: articles published in full for free; articles published in English, Portuguese and Spanish; publications between January 2016 and May 2021 and articles that fit the theme. Results: Based on this search strategy, 3,015 works were found in full; of these, 6 articles were duplicated in the search strategies, thus totaling 27 works selected after applying the inclusion and exclusion criteria. Final considerations: Low-intensity laser can be used in maxillofacial surgery because it has biological mechanisms that favor postoperative recovery, helping to reduce edema and painful symptoms.